PENEGAKAN HUKUM PENANGANAN GELANDANGAN DAN PENGEMIS MENURUT UNDANG-UNDANG DASAR 1945 DAN HUKUM PIDANA - Yusrizal Yusrizal (Jurnal Media Hukum, 2012)
The criminal law enforcement in handling the vagabonds and the beggars should be in harmony with the higher regulations and with the values of the living law. Moreover, the implementation of article 34 of the 1945 Constitution and the policy if the legal provisions in the law abiding in the society, such as the law of the national social security system and the law of people’s prosperity which can contribute to the abolishment of poverty. The result of the research showed that the functionalization of the criminal law (law enforcement) against the vagabonds and the beggars was not maximal enough because the process of putting the criminal law in to operation was directed to punishment and not to development. Hierarchically, article 504 and article 505 KUHP are not restricted and efficient use of its implementations because they are not contrary with the high regulation. In principle, the vagabonds and the beggars do not violate the law; it can be said that and action cannot be categorized as illegal if there is no illegal intention so that it is true when the action is de-discrimination because no one complains because of their action.Key words: Law Enforcement, Vagabonds, Beggars, 1945 Constitution, Criminal Code